ANALISIS HUKUM SENGKETA SERTIFIKAT GANDA BERDASARKAN UU NO. 30 TAHUN 2014 TENTANG ADMINISTRASI PEMERINTAHAN DAN PP NO. 24 TAHUN 1997 - Resa Sinta; Indah Ayu Wulandari; Dede Ika Murofikoh (JURNAL ILMIAH NUSANTARA, 2026)
Land certificates are an essential legal instrument that provides legal certainty over land rights and serves as the primary basis for land transactions in Indonesia. However, administrative weaknesses in the land registration system often lead to the issuance of duplicate land certificates for the same object, which results in legal uncertainty, ownership disputes, and a decline in public trust toward the state. Disputes over duplicate certificates constitute a serious legal problem because they involve administrative negligence, potential abuse of authority, and complex legal consequences across administrative, civil, and criminal domains. This research focuses on the analysis of the settlement of duplicate land certificate disputes based on Law Number 30 of 2014 on Government Administration and Government Regulation Number 24 of 1997 on Land Registration. The method used in this study is normative legal research, employing a statute approach and a case approach to examine relevant regulations and judicial decisions related to duplicate certificates. The results of the study indicate that the issuance of duplicate certificates reflects violations of the principles of good governance, particularly legal certainty, accuracy, and accountability. Therefore, land officials are required to exercise greater diligence and responsibility in the land registration process. Through proper application of administrative law principles and effective dispute resolution mechanisms, legal certainty and justice for affected parties can be restored in accordance with the rule of law.